الاستخفـاف: دراسة مفاهيمية قرآنية Istikhfaf: A Qur’anic Conceptual Study - أحمد (Fethi Ahmed) فتحي (At-Tajdid - Intellectual Refereed Journal, 2011)
مستخلص البحث تندرج هذه الدراسة لمفهوم الاستخفاف في القرآن الكريم في إطار الاهتمام بسبل تطوير مناهج ونظريات لفهم القرآن الكريم وإدراك بنائه الداخلي من أجل استنباط معاني ألفاظه وعباراته والوقوف على دلالاتها بصورة سليمة. وهي بذلك تسعى لإبراز هدي القرآن في المجال السياسي والاجتماعي لفهم بعض مظاهر الظلم السياسي ومآلاته ونتائجه الوخيمة على المجتمعات البشرية عامة والإسلامية خاصة. ولذلك ركز الباحث على تقصي مفهوم الاستخفاف في السياق القرآني، معتمدًا منهج الاستقراء وتحليل المضمون والتفسير الموضوعي والتحليل الدلالي. فحاول تتبع المعنى الأصلي للفعل "اسْتَخَفَّ" عند علماء اللغة ودلالاته في الاستعمال القرآني ومن خلال علاقته بألفاظ أخرى مقاربة له في الدلالة. وقد تم ذلك في إطار قصة فرعون كما عرضها القرآن، سعيًا للكشف عن الأبعاد والروابط المختلفة للاستخفاف مفهومًا وظاهرة. وقد استطاع البحث أن يجلي مدى خطورة الاستخفاف بوصفه موقفًا وسلوكًا وظاهرة في الحياة الاجتماعية والسياسية للبشر، وذلك من خلال شرح هذه الظاهرة كما عرضها القرآن الكريم في سياق الفعل السياسي الفرعوني. وقد بين البحث كذلك أن الاستخفاف بوصفه سلوكًا سياسيًّا لا يتم إلا بوجود مُستَخِفٍّ فاسد في ذاته وفكره، وظالم ومستكبر وعال ومسرف في سلوكه، وطاغ في صفاته بوصفه حاكمًا، كما بين أنه لا يتم الاستخفاف إلا بوجود أناس قابلين للاستخفاف لخفة عقولهم وضعف فكرهم، وفساد عقائدهم وانحطاط أخلاقهم وسلوكهم. وفضلاً عن ذلك أكدت الدراسة أن الاستخفاف ظاهرة مطردة في تاريخ البشر، فهي تتكرر في كل عصر إذا توافرت الشروط الذاتية والموضوعية المناسبة لنموها وسيطرتها مهما اختلفت الأساليب والأشكال، وأنه إذا وقع الاستخفاف وتجذر سياسيًّا واجتماعيًّا فإن سنة الله جارية ونافذة في المُستَخِف والمُستَخَف سواء بسواء، فيؤول حالهم إلى البوار والحسران المبين. الكلمات الأساسية: القرآن، التفسير الموضوعي، الاستخفاف، الظلم السياسي، النموذج الفرعوني في الحكم، السياسة، المجتمع، سنة الله. Abstract This study of the concept of istikhfÉf (underestimating, disparaging) in the Qur’an belongs to the preoccupation with developing methods and theories for understanding the Qur’an and comprehending its internal structure in order to discover the meanings of its words and expressions and grasp their significations in a proper manner. Thus it aims at bringing to the fore the Qur’an’s guidance with regard to the political and social sphere as a means to understanding some aspects of political injustice and oppression and its pernicious consequences for human societies in general and Muslim societies in particular. For this the author has focused on exploring the concept of istikhfÉf in the Qur’anic context by employing inductive inference, thematic interpretation and semantic and content analysis. Hence he investigated the original meaning of the verb istakhaffa (to underestimate, to disparage, to incite to levity) according to Arab philologists and its meanings in the Qur’anic usage and in relation with other close terms. All this has been done in the context of the story of the Pharaoh as narrated by the Qur’an so as to uncover the various dimensions and correlations of istikhfÉf both as a concept and phenomenon. By analyzing the subject in question as described by the Qur’an in its account on the political bahaviour of the Pharaoh, the study has shown how grave istikhfÉf is in the social and political life of humanity as an attitude, type of conduct and phenomenon. The study has also shown that istikhfÉf as a political behaviuor can only happen when there is a mustkhif (a political leader belittling and disparaging his people) who is corrupt in himself and his thinking, arrogant, insolent and oppressive as a leader. It has equally shown that istikhfÉf does not occur and prevail unless the people are prone to be underestimated and disparaged due to their weak-mindedness and frivolous thinking as well as corruption in their beliefs and decadence, morality and conduct. Moreover, the study argued that istikhfÉf is a regular phenomenon in human history, thus occurring in any place at anytime, whenever the psychological factors and external circumstances conducive to it are present, no matter how its forms are. Then God’s decree befalls society when it succumbs to istikhfÉf as it takes roots in the political and social domains, thus bringing it to ruin and utter loss and sparing none of its parties. Key terms: Qur’an, thematic interpretation istikhfÉf, politics, society, political oppression, Pharaoh’s model of governance, God’s decree. legislation, historicism Abstrak Listen Read phonetically Kajian tentang konsep istikhfÉf (meremehkan, meremehkan) dalam Al-Qur’an milik keasyikan dengan mengembangkan kaedah dan teori-teori untuk memahami Al-Qur’an dan memahami struktur dalaman dalam rangka untuk mencari erti kata-kata dan ekspresi dan pegang mereka makna dengan cara yang betul. Oleh kerana itu bertujuan untuk membawa kedepan bimbingan Al-Qur’an berkaitan dengan bidang politik dan sosial sebagai sarana untuk memahami beberapa aspek ketidakadilan politik dan penindasan dan akibat merosakkan bagi masyarakat manusia secara umum dan masyarakat muslim pada khususnya. Untuk ini penulis telah difokuskan pada eksplorasi konsep istikhfÉf dalam konteks Al-Quran dengan menggunakan inferensi induktif, tafsiran tematik dan analisis semantik dan kandungan. Maka ia menyiasat erti asli dari istakhaffa kata kerja (untuk meremehkan, untuk menghasut untuk kesembronoan) menurut filologi Arab dan arti dalam penggunaan Al-Quran dan sehubungan dengan hal berhampiran yang lain. Semua ini telah dilakukan dalam konteks kisah Firaun yang diriwayatkan oleh Al-Quran sehingga dapat mengungkap pelbagai dimensi dan korelasi istikhfÉf baik sebagai konsep dan fenomena. Dengan menganalisis subjek dalam soalan seperti yang dijelaskan oleh Al-Quran terhadap bahaviour politik Firaun, kajian telah menunjukkan bagaimana maqam istikhfÉf dalam kehidupan sosial dan politik kemanusiaan sebagai sikap, jenis perilaku dan fenomena. Penyelidikan ini juga menunjukkan bahawa istikhfÉf sebagai perilaku politik hanya boleh berlaku apabila ada mustkhif (pemimpin politik meremehkan dan meremehkan rakyatnya) yang korup dalam dirinya dan pemikirannya, sombong, kurang ajar dan menindas. Hal ini juga menunjukkan bahawa istikhfÉf tidak berlaku dan berlaku kecuali untuk orang cenderung untuk dianggap remeh kerana lemah fikiran mereka dan berfikir sembrono serta korupsi dalam, moral kepercayaan mereka dan perilaku. Selain itu, kajian ini berpendapat bahawa istikhfÉf merupakan fenomena biasa dalam sejarah manusia, sehingga terjadi di mana saja kapan saja, jika faktor psikologi dan keadaan luaran yang kondusif untuk itu hadir, tidak peduli bagaimana bentuk perlembagaanya. Kemudian keputusan Allah menimpa masyarakat ketika menyerah untuk istikhfÉf kerana akar dalam domain politik dan sosial, sehingga membawanya untuk kerosakan dan kerugian. Kata kunci: Al-Qur’an, tafsiran istikhfÉf tematik, politik, masyarakat, penindasan politik, model Firaun kerajaan, keputusan Allah.